1999
DOI: 10.1046/j.1440-1681.1999.02990.x
|View full text |Cite
|
Sign up to set email alerts
|

Living in the Cold: Freeze‐induced Gene Responses in Freeze‐tolerant Vertebrates

Abstract: 1. Winter survival for numerous cold-blooded animals includes freeze tolerance: the ability to endure the conversion of as much as 65% of total body water into extracellular ice. Selected molecular adaptations underlying freeze tolerance (e.g. cryoprotectants, ice nucleating proteins) have been widely studied, but the full range of metabolic adjustments needed for freeze endurance remains unknown. 2. Recent studies using gene screening techniques are providing a different approach to the search for biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Natural freezing survival involves coordinated adjustments to metabolism to allow organisms to endure the multiple stresses (prominently including ischemia and cellular volume reduction) associated with the freezing of extracellular body fluids. Selected biochemical adaptations have been extensively studied (e.g., glucose use as a cryoprotectant; energy metabolism) (1,2), but the recent application of gene screening technology is allowing for the identification of other contributing factors (3,6). The present study describes the up‐regulation of a novel gene, li16 , during freezing and analyzes the influences on its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Natural freezing survival involves coordinated adjustments to metabolism to allow organisms to endure the multiple stresses (prominently including ischemia and cellular volume reduction) associated with the freezing of extracellular body fluids. Selected biochemical adaptations have been extensively studied (e.g., glucose use as a cryoprotectant; energy metabolism) (1,2), but the recent application of gene screening technology is allowing for the identification of other contributing factors (3,6). The present study describes the up‐regulation of a novel gene, li16 , during freezing and analyzes the influences on its expression.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most critical strategies for freeze tolerance involves the synthesis of high amounts of low-molecular-weight carbohydrates (glucose in wood frogs), which provide colligative resistance to detrimental decreases in cell volume while also serving to stabilize the phospholipid bilayer of membranes and to restrict the formation of intracellular ice [112-114]. Importantly, research has shown that simple augmentation strategies such as increasing endogenous levels of cryoprotectants (via injection) prior to freezing have the capacity to improve survival and extend the time in a frozen state in a certain context from 2 weeks to 49 days [113].…”
Section: High-subzero Preservationmentioning
confidence: 99%
“…Freezing imposes several challenges including: (A) physical stress as a result of ice crystal formation in the extracellular matrix and between organs which may be damaging to the architectural integrity of the cells and capillaries, (B) anoxic/ischemic stress to organs as a result of decrease in oxygen delivery due to blood plasma being frozen (C) dehydration stress as a result of losing up to ~60-70% of total body water to freezing resulting in organ dehydration and an increase in osmolality and ionic strength, and finally (D) physiological stress as a result of prolonged inactivity, complete cessation of heart beat, breathing, and brain activity (Storey, 1999;Storey & Storey 2004a, 2004b. Furthermore, these organisms have to also deal with challenges associated with thawing such as a large influx of reactive oxygen species upon oxygen reperfusion, cellular rehydration, and disuse of skeletal muscles during prolonged periods of inactivity.…”
Section: Adaptations To Sub-zero Temperaturesmentioning
confidence: 99%
“…In fact, the same study showed that wood frogs that hibernate in damp hibernacula lose only 2.5% of their total body water to evaporation while those that hibernate without covers will lose ~50% of their total body water in the same period of freezing (Churchill & Storey, 1993). Dehydration provides great benefits for wood frogs during freezing, it limits the amount of free water available and attenuates ice growth within the organs, thereby preventing intracellular ice formation (Storey, 1999). Wood frogs confine ice growth within the extra-organ space, abdominal cavity, the bladder, and/or between the skeletal muscle and the skin thus limiting cellular damage to tissues and capillaries (Storey, 1999).…”
Section: 5anoxia and Dehydrationmentioning
confidence: 99%
See 1 more Smart Citation